Bioactivity-guided identification of flavonoids with cholinesterase and β-amyloid peptide aggregation inhibitory effects from the seeds of Millettia pachycarpa. Issue 10 (15th May 2019) - Tu, Yanbei; Wu, Chuanhai; Kang, Yunyao; Li, Qin; Zhu, Chao; Li, Yanfang
Graphical abstract: Highlights: The anti-AD effects of different solvent extracts of M. pachycarpa were firstly reported. An unusual oxidative ring-opening skeleton rotenoid and nine known flavonoids were obtained. Four compounds showed strong inhibitory activities on cholinesterase. Strong binding affinities of active compounds to cholinesterase were confirmed by fluorescence quenching. Two compounds exhibited potent inhibitory effects against Aβ1-42 aggregation. Abstract: Millettia pachycarpa Benth, a widely used anthelminthic drug in folk, is rich in flavonoids with various bioactivities. This study aimed to identify active flavonoids with anti-Alzheimer's disease (AD) effect from its seeds by a bioassay-guided isolation. A novel rotenoid with unusual oxidative ring-opening skeleton (10 ) and nine known flavonoids (1 –9 ) were obtained, and their structures were elucidated by NMR and HR-ESIMS analysis. Among all isolates, 7 and 8 showed selective butyrylcholinesterase (BChE) inhibitory activities (IC50 = 2.34 and 11.49 μM, respectively), while 3 was classified as a dual-action inhibitor against acetylcholinesterase (AChE) and BChE (IC50 AChE = 17.14 μM, IC50 BChE = 5.68 μM). Further kinetic study revealed that 3, 7, and 8 were mixed-type BChE inhibitors, but 3 was a competitive AChE inhibitor. Their strong binding affinities to BChE were confirmed by fluorescence quenching analysis. Additionally, 3 and 8 exhibited potent inhibitory effects against β-amyloid peptide aggregation. These results revealed M. pachycarpa could be a valuable source for anti-AD leads development, and compounds 3, 7 and 8 were worthy of further study as multifunctional or specific agents for AD treatment.